Effect of Stevia rebaudiana Bertonni Leaves powder on Lipid Profiles and Productive Parameters of Laying Hens - Paredes-López, Daniel (2019)
Eggs are sources of high nutritious value; however, their intake is associated with hypercholesterolemia in consumers. Stevia rebaudiana, among other properties, has a hypoglycemic and hypocholesterolemic effect in humans, rats and broilers chicken. The objectives of this research were to determine the effect of the inclusion of 0, 1, 2 and 3% of Stevia rebaudiana leaves powder in the diet on the lipid profile and productive parameters of Isa Brown hens. One hundred, 17 - 24 week old, Isa Brown laying hens were used and distributed in a completely randomized design with four treatments and five repetitions. The increase in the levels of powder from Stevia leaves decreased the cholesterol profile (p < 0.05), without changing other profiles and the productive parameters (p > 0.05). Additionally, the triglyceride profile and weight gain showed quadratic and negative linear tendencies, respectively associated with the increase of powder from Stevia leaves in the diet. It is concluded that the levels of cholesterol, triglycerides, final weight and total weight gain of Isa Brown laying hens has a tendency to decrease when the levels of powder from Stevia leaves is increased in the diet.